Proposed Domains for Assessing Postpartum Recovery: A Concept Elicitation Study. Issue 4 (21st December 2022) - Sultan, P.; Jensen, S.E.; Taylor, J.; El-Sayed, Y.; Carmichael, S.; Cella, D.; Angst, M.S.; Gaudilliere, B.; Lyell, D.J.; Carvalho, B.
Abstract : ( BJOG . 2022;129:9–20) Although ~3.8 million people have children per year, few people have researched postpartum recovery. This may be because tools developed to measure postpartum recovery, such as the Obstetric Quality of Recovery instrument, have not been used, validated, or developed sufficiently. The authors of this study previously created a list of domains they considered valuable to postpartum recovery, but had not determined which are important to stakeholders, postpartum individuals, obstetricians, maternal and fetal medicine specialists, nurses, and obstetric anesthetists. This study aimed to identify and propose a list of domains, rank these domains based on perspectives and feedback from stakeholders, identify factors that positively and negatively impact postpartum recovery, and establish the greatest difficulties individuals face after childbirth through concept elicitation interviews and focus group meetings.